Frequency of CYP2B6 Alleles in Major Iranian Ethnicities, Affecting Response to Efavirenz - Parham Mardi; Bahareh Tavakoli-Far; Samira Sheibani Nia; Roshanak Jazayeri; Massoud Houshmand (Genetics Research)
Introduction. Efavirenz is an antihuman immunodeficiency virus (HIV) drug metabolized by cytochrome P450 2B6 (CYP2B6) enzyme. Cytochrome P450 2B6 is an enzyme that in humans is encoded by the CYP2B6 gene. Polymorphisms of this gene play a crucial role in the metabolism of drugs such as Efavirenz. This study aims to evaluate the frequency of three clinically significant CYP2B6 polymorphisms (CYP2B6∗6 (516G > T), CYP2B6∗4 (785A > G), and CYP2B6∗5 (1459C > T)) in three major Iranian ethnicities. Methods. One hundred forty-seven participants from three main Iranian ethnicities were included in this study. After DNA extraction, CYP2B6∗6 (516G > T), CYP2B6∗4 (785A > G), and CYP2B6∗5 (1459C > T) were genotyped using tetra-primer amplification refractory mutation system polymerase chain reaction (ARMS-PCR). Results. The frequency of the mutated allele in the Iranian population for CYP2B6∗6 (516G > T) was 41.50 (95% CI: 35.81, 47.36), which was significantly lower than in Kurds (59.62, 95% CI: 45.10, 72.99). Similarly, Kurds had a higher frequency of mutated allele of CYP2B6∗5 (1459C > T) (46.15%, 95% CI: 32.23, 60.53) than in Iranians (24.49%, 95% CI: 19.68, 29.82). The frequency of A and G alleles of CYP2B6∗4 (785A > G) was 62.59% (95% CI: 56.78, 68.13) and 37.41 (95% CI: 31.87, 43.22), respectively. Conclusion. Kurds are at higher risk of adverse drug reactions (ADRs) and insufficient anti-HIV response compared to other Iranians.